Association study of genetic variation in the autophagy lysosome pathway genes and risk of eight kinds of cancers. Issue 1 (16th February 2018) - Tan, Juan; Fu, Linna; Chen, Haoyan; Guan, Jian; Chen, Yingxuan; Fang, Jingyuan
Abstract : The autophagy lysosome pathway is essential to maintain cell viability and homeostasis in response to many stressful environments, which is reported to play a vital role in cancer development and therapy. However, the association of genetic alterations of this pathway with risk of cancer remains unclear. Based on genome‐wide association study data of eight kinds of cancers, we used an adaptive rank truncated product approach to perform a pathway‐level and gene‐level analysis, and used a logistic model to calculate SNP‐level associations to examine whether an altered autophagy lysosome pathway contributes to cancer susceptibility. Among eight kinds of cancers, four of them showed significant statistics in the pathway‐level analysis, including breast cancer ( p = 0.00705), gastric cancer ( p = 0.00880), lung cancer ( p = 0.000100) and renal cell carcinoma ( p = 0.00190). We also found that some autophagy lysosome genes had signals of association with cancer risk. Our results demonstrated that inherited genetic variants in the overall autophagy lysosome pathway and certain associated genes might contribute to cancer susceptibility, which warrant further evaluation in other independent datasets. Abstract : What's new? The autophagy lysosome pathway is suspected of playing a role in cancer initiation. Whether genetic variants of autophagy lysosome genes are associated with cancer risk, however, remains unclear. In this systematic analysis of datasets from eight genome‐wide association studies, germ‐line polymorphic variants in the autophagy lysosome pathway were identified as important susceptibility factors specifically for four cancer types: lung cancer, gastric cancer, breast cancer, and renal cell carcinoma. In particular, several genes in the pathway were significantly associated cancers of the breast and lung. The results warrant further investigation of autophagy lysosome pathway involvement in cancer pathogenesis and risk.